2005
DOI: 10.1002/sim.2216
|View full text |Cite
|
Sign up to set email alerts
|

Confidence interval construction for proportion difference in small‐sample paired studies

Abstract: Paired dichotomous data may arise in clinical trials such as pre-/post-test comparison studies and equivalence trials. Reporting parameter estimates (e.g. odds ratio, rate difference and rate ratio) along with their associated confidence interval estimates becomes a necessity in many medical journals. Various asymptotic confidence interval estimators have long been developed for differences in correlated binary proportions. Nevertheless, the performance of these asymptotic methods may have poor coverage proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…With respect to published work in the Statistics in Medicine, see, e.g. References [1][2][3][4][5][6]. In all of these papers, the statistical distribution of the differences of proportions appears to have been approximated by some simple form, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to published work in the Statistics in Medicine, see, e.g. References [1][2][3][4][5][6]. In all of these papers, the statistical distribution of the differences of proportions appears to have been approximated by some simple form, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical results given by Tango [18] and Newcombe [12] demonstrated that the profile-likelihood-based and score-test-based confidence intervals performed satisfactorily in large sample designs. Tang et al [16] empirically demonstrated that Tango score confidence interval performed unsatisfactorily in small-sample designs and developed an exact unconditional and an approximate unconditional confidence intervals for proportion difference in small-sample paired studies. However, all the aforementioned work were confined to matched-pair data without incomplete data.…”
Section: Introductionmentioning
confidence: 99%
“…Define X = 1 if a patient vomited at least once during the last six-hour period (i.e., hour 18-24) after receiving MPRED; = 0 otherwise, and Y = 1 if a patient vomited at least once during the last six-hour period after receiving METCLO; = 0 otherwise. It was reported that amongst the 157 eligible patients, (i) 115 received both treatments in the two cycles (i.e., with both X and Y being observed); (ii) 16 received only MPRED for the first cycle but not METCLO for the second cycle (i.e., with only X being observed); and (iii) 26 received only METCLO for the first cycle but not MPRED for the second cycle (i.e., with only Y being observed). For scenario (i), it was reported that 106 patients experienced at least one vomiting in either treatment (i.e., 115 − 106 = 9 patients had no vomiting experience).…”
Section: Introductionmentioning
confidence: 99%
“…Tango [7] presented the profile-likelihood-based confidence interval and the score-test-based confidence interval for risk difference in paired-design studies on the basis of asymptotic theories, and some empirical results given in Tango [8] and Newcombe [9] indicated that the profile-likelihood-based confidence interval and the score-test-based confidence interval perform satisfactorily in large-sample designs. Tang et al [10] noted that Tango's [7] confidence intervals perform unsatisfactorily in small-sample designs. Therefore, Tang et al [10] developed an exact unconditional confidence interval and an approximate unconditional confidence interval for proportion difference in small-sample paired studies.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al [10] noted that Tango's [7] confidence intervals perform unsatisfactorily in small-sample designs. Therefore, Tang et al [10] developed an exact unconditional confidence interval and an approximate unconditional confidence interval for proportion difference in small-sample paired studies. However, all the above cited works are confined to a single 2×2 table, and there is little work for confidence interval construction in multiple 2×2 tables.…”
Section: Introductionmentioning
confidence: 99%